Microsoft Corp. : branding and positioning .NET - Sawhney, Mohanbir, (SAGE Knowledge. Cases., 2017)
John Williams, senior director of marketing for Microsoft's .NET, was trying to build the .NET brand, a comprehensive family of next-generation connectivity software products. Highlights the challenges of branding and positioning a complex technology offering. The first challenge facing Microsoft was to develop a common definition of .NET, which had been in flux over the prior two years. The second challenge was to choose between an umbrella branding strategy, a sub-branding strategy, and an ingredient branding strategy. The third challenge was to create a value proposition that would appeal to three very different target audiences: business decision makers, IT professionals, and developers.